Methotrexate Inhibits T Cell Proliferation but Not Inflammatory Cytokine Expression to Modulate Immunity in People Living With HIV - Freeman, Michael L.; Clagett, Brian M.; Moisi, Daniela; Yeh, Eunice; Morris, Charles D.; Ryu, Angela; Rodriguez, Benigno; Stein, James H.; Deeks, Steven G.; Currier, Judith S.; Hsue, Priscilla Y.; Anthony, Donald D.; et al. (Frontiers in Immunology, 2022)
Inflammation associated with increased risk of comorbidities persists in people living with HIV (PWH) on combination antiretroviral therapy (ART). A recent placebo-controlled trial of low-dose methotrexate (MTX) in PWH found that numbers of total CD4 and CD8 T cells decreased in the low-dose MTX arm. In this report we analyzed T cell phenotypes and additional plasma inflammatory indices in samples from the trial. We found that cycling (Ki67+) T cells lacking Bcl-2 were reduced by MTX but plasma inflammatory cytokines were largely unaffected. In a series of in vitro experiments to further investigate the mechanisms of MTX activity, we found that MTX did not inhibit effector cytokine production but inhibited T cell proliferation downstream of mTOR activation, mitochondrial function, and cell cycle entry. This inhibitory effect was reversible with folinic acid, suggesting low-dose MTX exerts anti-inflammatory effects in vivo in PWH largely by blocking T cell proliferation via dihydrofolate reductase inhibition, yet daily administration of folic acid did not rescue this effect in trial participants. Our findings identify the main mechanism of action of this widely used anti-inflammatory medicine in PWH and may provide insight into how MTX works in the setting of other inflammatory conditions.